Shine bright : a very personal history of Black women in pop - Smith, Danyel (Roc Lit 101, One World, 2022)
"From one of the preeminent cultural critics of her generation, a radiant weave of memoir, criticism, and biography that tells the story of black women in music--from the Dixie Cups to Gladys Knight to Janet, Whitney, and Mariah-- as the foundational story of American pop"--